Utilization of Smartphone Technology and Wearable Technology Following TKA - Gordon, Adam M.; Hussain, Awais; Mont, Michael A. (The Journal of Knee Surgery, 2025)
The widespread adoption of smartphones and wearable technology has introduced innovative approaches in health care, particularly in postoperative rehabilitation. These technologies hold significant promise for improving recovery following lower extremity arthroplasty, especially total knee arthroplasty (TKA). Despite growing interest, the evidence on their effectiveness and long-term impact remains variable.This narrative review evaluates the utilization of smartphone applications, wearable devices, and their combined use in postoperative recovery after TKA. Key studies assessing adherence, functional outcomes, patient satisfaction, and health care utilization were analyzed to synthesize insights into their effectiveness compared to traditional rehabilitation approaches.Smartphone applications have demonstrated improvements in adherence to rehabilitation plans, pain management, and functional outcomes. For instance, interventions using text-based prompts or interactive platforms enhanced physical activity, reduced narcotic use, and improved patient-reported outcomes such as PROM adherence and range of motion (ROM). Similarly, wearable devices provided accurate feedback on activity levels and step counts, promoting early mobility and strength recovery. Combined approaches leveraging both technologies further enhanced adherence, functional recovery, and patient engagement while reducing health care utilization.The integration of smartphone and wearable technologies in TKA rehabilitation shows potential for improving recovery outcomes. While findings generally indicate noninferiority or superiority to conventional methods, limitations exist in standardization, data accuracy, and long-term benefits. Future research should focus on refining these technologies, establishing standardized guidelines, and evaluating their cost-effectiveness in diverse populations. Smartphone and wearable technologies represent safe and effective tools for enhancing postoperative outcomes in TKA patients. Their integration into clinical practice could optimize rehabilitation protocols, improve patient engagement, and potentially reduce health care costs.
Keywords: smartphone applications; sensors; technology; rehabilitation; total knee arthroplasty